EVALUATION CRITERIA OF A BOTH BUYER IN CIVIL LAW - Глушков, Валентин (SWorldJournal, 2024)
Despite the fact that good faith (bona fides) is mentioned even in Roman law and all this time the continuous development of this category continues, disputes related to the determination of the legal status of the acquirer of property (bona fide or unscr